2019
DOI: 10.1097/cnq.0000000000000267
|View full text |Cite
|
Sign up to set email alerts
|

Room Design—A Phenomenological-Hermeneutical Study

Abstract: Medical technology has progressed tremendously over the last few decades, but the same development cannot be seen in the design of these intensive care unit environments. Authors report results of a study of evidence-based room design, emphasizing the impact on conveying a caring attitude to patients. Ten nonparticipant observations were conducted in patient rooms with 2 different designs, followed by interviews. The data were analyzed using a phenomenological-hermeneutical approach. The results did not reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In a survey of 42 families of ICU patients, Ulrich et al (2019) found that access to and breaks in a flowery hospital garden reduced stress, and promoted relaxation and well-being for the visiting family to a higher degree than when they had a break in the hospital café or waiting area. These findings have also been endorsed in a study investigating the connection between acts of caring and the design of the ICU patient room (Sundberg et al, 2019). In this study, the authors stress the importance of a supportive environment and of nurses acquiring an attentive and attuned gaze and attention to the suffering person.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…In a survey of 42 families of ICU patients, Ulrich et al (2019) found that access to and breaks in a flowery hospital garden reduced stress, and promoted relaxation and well-being for the visiting family to a higher degree than when they had a break in the hospital café or waiting area. These findings have also been endorsed in a study investigating the connection between acts of caring and the design of the ICU patient room (Sundberg et al, 2019). In this study, the authors stress the importance of a supportive environment and of nurses acquiring an attentive and attuned gaze and attention to the suffering person.…”
Section: Discussionmentioning
confidence: 60%
“…In a review of literature collected from nursing, medicine, psychology, architecture and environmental science, Minton and Batten (2016) and sound reduction, facilitating access to daylight and placing the bed to give the patient a view of natural scenery. These components were among those taken into consideration in a Swedish ICU complex intervention programme focussing on healing environments and evidence-based design in ICUs (Engwall et al, 2015;Johansson et al, 2017;Sundberg et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ICUs are shared places in terms of being places for care, treatment, rest and recovery for the patient while also being a workplace and a visiting room [ 54 , 55 ]. Due to their high‐tech character, ICUs can be overwhelming places.…”
Section: Place Space and Icumentioning
confidence: 99%
“…10,15 Ultimately, it is recommended that a balance exist between fixed items standardized for consistency and mobile elements to support rapid reconfiguration of the caregiving environment. 17 The FGI guidelines state that each patient shall have access to a toilet room without having to enter the general corridor area. 14 Moreover, the inclusion, positioning, and configuration of the bathroom within the patient room are primary issues to consider.…”
Section: Patient Room Configurationsmentioning
confidence: 99%